1988
DOI: 10.1677/joe.0.1170229
|View full text |Cite
|
Sign up to set email alerts
|

Induction of LH hypersecretion in cyclic rats during the afternoon of oestrus by oestrogen in conjunction with progesterone antagonism or opioidergic blockade

Abstract: The pro-oestrous secretion of progesterone that follows the LH surge in the rat limits the expression of the daily signal for LH surge initiation until the following oestrous cycle. This study explored the role of endogenous opioid peptides in the extinction by progesterone of the signal for the LH surge induced by oestrogen. Intact cyclic rats underwent external jugular venous cannulation on dioestrus, and were allowed to elicit a spontaneous pro-oestrous LH surge. On the afternoon of pro-oestrus, rats receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…As with a number of other estrogen-induced processes at the time of the LH surge in the rat (19), progesterone facilitates the effects of estrogen and initially promotes the afternoon decline in ␤END activity within the GnRH network (19,386,388,389). However, the marked increase in progesterone concentrations that follows the onset of the LH surge exerts an opposite effect to estrogen on these cells and increases ␤END mRNA levels (381,383).…”
Section: June 1998 Estrogen Inputs To Gnrh Neurons 315mentioning
confidence: 98%
See 1 more Smart Citation
“…As with a number of other estrogen-induced processes at the time of the LH surge in the rat (19), progesterone facilitates the effects of estrogen and initially promotes the afternoon decline in ␤END activity within the GnRH network (19,386,388,389). However, the marked increase in progesterone concentrations that follows the onset of the LH surge exerts an opposite effect to estrogen on these cells and increases ␤END mRNA levels (381,383).…”
Section: June 1998 Estrogen Inputs To Gnrh Neurons 315mentioning
confidence: 98%
“…However, the marked increase in progesterone concentrations that follows the onset of the LH surge exerts an opposite effect to estrogen on these cells and increases ␤END mRNA levels (381,383). This is suggested to be the neural mechanism through which progesterone inhibits the occurrence of a further estrogen-induced LH surge on estrus (386,389). Progesterone has similarly been suggested to utilize ␤END neurons to inhibit LH secretion in the sheep (4).…”
Section: June 1998 Estrogen Inputs To Gnrh Neurons 315mentioning
confidence: 99%
“…It has been shown that administration of RU486 to female cyclic rats dissociates dioestrous secretion of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) (Sánchez-Criado et al 1990, reduces the magnitude of the preovulatory LH surge (Rao & Mahesh 1986, Sánchez-Criado et al 1990) and abolishes the primary and secondary surge of FSH (Knox & Schwartz 1992, Knox et al 1993, Sánchez-Criado et al 1994. These effects of RU486 on FSH and LH secretion could be the result of the blockade of progesterone and/or glucocorticoid action (Lusting et al 1988, Tébar et al 1995. Also, results from recent experiments indicate that RU486 may affect FSH (Szabo et al 1996, Ringstrom et al 1997 and LH (Waring & Turgeon 1992, Turgeon & Waring 1994, Levine 1997 secretion through the blockade of ligand-independent activation of progesterone receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exogenous P administered to ovariectomized estrogen-primed rats extinguishes the ability of the hypothalamus to generate daily LH surges [26, 27]. Little [28]or no attention [16, 24, 25, 29, 30, 31, 32, 33]has been paid to the proestrous afternoon P action on the secretion of FSH on estrous afternoon. To our knowledge the data from the present study are the first to deal with the effects of LH-dependent progesterone secretion on proestrous afternoon on FSH secretion the following day.…”
Section: Discussionmentioning
confidence: 99%